(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
The future of the nursing profession is bright. The rise of technological advances that fuel the need for more skilled nursing care that provides an opportunity to be creative and innovative in addressing and finding solutions to current issues. (Banova, 2019) further opens doors of opportunities. Responding to this concern, this study described the nurses’ lived experiences about evidence-based practice in the emergency department as a basis for innovations in nursing education. The Husserlian phenomenological design was utilized with the 10 respondents, who were purposively sampled using the following inclusion criteria: must be registered nurses of any age, nurses working at the emergency department of the five different hospitals in the province of Ilocos Sur with a minimum work experience of at least 2 years in the facility in any employment status. The data gathering procedures included a combination of one-on-one interviews and observation, and Giorgi’s method of interpretation was used in analyzing the data gathered. The result of the study highlighted four themes: A Torch-lit Path, An Invisible Journey, Bold and Plain, and a Radiant End. These themes captured the experiences and realization of the ER nurses on the importance of evidence-based practice in their respective institutions. They recognized this as a tunnel that they need to pass through despite the darkness of the said tunnel. The findings of this study can be used not only as a blueprint for further research in this field but also as a catalyst in discussing future issues in the Philippine nursing society and can be of help in the further advancement of the nursing profession and promoting evidence-based practices through clinical practices and exposures.